Evaluation Circular Failure of Soil Slopes Using Classification and Predictive Gene Expression Programming Schemes - Hanandeh, Shadi (Frontiers in Built Environment, 2022)
This paper presents an analysis of a dataset related to slope stability circular failure cases using the Gene Xpro Tools program. Two models were developed, the first model was utilized to find a classification model that shows the stability status (S). The second model is utilized to estimate the factor of safety and predict the mathematical model to serve as an indicator of slope stability. The proposed models include cohesion, unit weight, slope angle, coefficient of pore water pressure, internal friction angle, slope height, internal friction angle, and safety factor. The results showed that the values of accuracy and error were 93.1% and 6.9%, respectively, for the classification model 1. The relationship between the actual values of the factor of safety and the output of Model 2 was an R2 value of 0.96. The models developed were subjected to a sensitivity analysis to determine the input variables' impact on output for the two models. The selected slope locations with different material characterizations were introduced into the geox5 software, and the results were compared to the two developed models. Also, in comparison to the developed models, the results matched and performed well.